Progress of Alkaline Anion Exchange Membranes for Fuel Cells: The Effects of Micro-Phase Separation - Xu, Fei; Su, Yue; Lin, Bencai (Frontiers in Materials, 2020)
Compared with that of proton exchange membrane fuel cells (PEMFCs), alkaline anion exchange membranes fuel cells (AEMFCs) with alkaline anion exchange membranes (AEMs) as electrolyte, are attracting more and more attention due to their potential use of nonprecious catalysts. As one of the key components of AEMFCs, an ideal AEM must possess high hydroxide conductivity, good thermal stability, sufficient mechanical stability and excellent long-term durability at elevated temperatures under alkaline environment. Until now, a large amount of AEMs with various chemical structures and properties have been prepared and studied in detail, and it is found that the micro-phase separation structure greatly affected the performance of AEMs. This mini-review provides recent progresses of AEMs with hydrophilic/hydrophobic micro-phase separation structure. The hydroxide conductivity, alkaline stability and mechanical properties of AEMs could be improved due to the formation of hydrophilic/hydrophobic micro-phase separation in membranes. The relationship among micro-phase separation structure, the chemical structures of polymers and the performance of membranes have been discussed in detail. The attempt of this article is to give an overview of some key factors for future design of novel AEMs with excellent performance such as high conductivity and improved chemical stability.